Mechanics of Biological Systems and Materials, Volume 6 Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics - Tekalur, Srinivasan Arjun; Zavattieri, Pablo; Korach, Chad S. (Conference Proceedings of the Society for Experimental Mechanics Series,, 2016)
5thInternational Symposium on the Mechanics of Biological Systems and Materials, Volume 6 of the Proceedings of the 2015SEM Annual Conference& Exposition on Experimental and Applied Mechanics, the sixth volume of nine from the Conference, brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on a wide range of areas, including:  Soft Tissues Mechanics Bio-Engineering and Biomechanics Natural Materials & Bio-Inspiration Novel Techniques and Experiments in Biomechanics Tissue Engineering Cells Mechanics.